Z problematyki "porozumień" w prawie pracy: [On "agrements" in labor law] (Studia Prawnicze / The Legal Studies, 1981)
Both in Labor law provisions and in literature the term "agreement" is used either to mean a duty to act in particular way ("in agreement with" other subjects), or the results of bipartial acts. While discussing these problems the Author concentrates on two issues: the meaning of certain terms used by the legislator (such as e.g. "in agreement with"), and closer characteristics and classification of bipartial agreements entered into by the representative of employers and trade unions.The contents and scope of the duty of a subject acting "in agreement with" nother is determined by the regulation of: the aim that is to be attained by a given subject; the scope of its autonomy in realizing that aim; obligatory participation of trade unions in the process of realization of the aim; and legal consequences of the lack of such participation. In the sphere of creating labor law norms this term means only the duty of the legislator to consider opinion of trade unions! On the other hand, in the sphere of practical application of labor law the term "in agreement with" cannot be construed in that way because often participation of trade unions is a legal (substantial) prerequisite of efficacity of making a given decision (e.g. article 177 § 1 of labor law code).In labor law agreements are created in result of bipartial acts and entered into on the basis of a congruent declaration of will of two equal, independent and autonomously operating subjects. They may regulate an individual, concrete social labor relationship or relations closely connected with it (e.g. agreements changing terms of work), or else, they may regulate such relations in a general and abstract way (e.g. collective labor agreements). Considering the subject-matter of such agreements, they may be deviided into: individual and collective. Among collective agreements we can distinguish: normative agreements constituting the source of legal norms for the parties themselves and third parties as well (e.g. workplaces and employees), and obligational agreements constituting the source of , obligations only for the parties to it.